Material characterization and finite element modelling of cyclic plasticity behavior for 304 stainless steel using a crystal plasticity model - Lu, Jiawa; Sun, Wei; Becker, Adib A. (Elsevier, 2016)
Low cycle fatigue tests were carried out for a 304 stainless steel at room temperature. A series of experimental characterisations, including SEM, TEM, and XRD were conducted for the 304 stainless steel to facilitate the understanding of the mechanical responses and microstructural behaviour of the material under cyclic loading including nanostructure, crystal structure and the fractured surface. The crystal plasticity finite element method (CPFEM) is a powerful tool for studying the microstructure influence on the cyclic plasticity behaviour. This method was incorporated into the commercially available software ABAQUS by coding a UMAT user subroutine. Based on the results of fatigue tests and material characterisation, the full set of material constants for the crystal plasticity model was determined. The CPFEM framework used in this paper can be used to predict the crack initiation sites based on the local accumulated plastic deformation and local plastic dissipation energy criterion, but with limitation in predicting the crack initiation caused by precipitates.